Hospital Characteristics Affect Consent and Conversion Rates for Potential Organ Donors. Issue 4 (April 2017) - Ali, Jawad T.; Ebadat, Aileen; Martins, Danilo; Ali, Sadia; Horton, Shannon; Coopwood, Thomas B.; Brown, Carlos V.R.
Consent and conversion rates of potential organ donors in the United States need to be maximized to match the number of individuals awaiting organ donation. Studies to date have not focused on characteristics of centers with better outcomes. We performed an 8-year (2006–2014) retrospective study of our local organ procurement organization database. We categorized hospitals in our region as academic centers versus nonacademic centers, trauma centers versus nontrauma centers, and large (≥400 beds) centers versus small (<400 beds) centers. We also compared trauma centers with Level I designation to all other centers. Primary outcomes included consent and conversion rates for potential organ donors. There were 22, 732 referrals to our organ procurement organization that resulted in 1, 057 eligible deaths. When comparing academic to nonacademic hospitals, academic hospitals had higher consent (71% vs 59%, P < 0.0001) and conversion (73% vs 64%, P = 0.008) rates. Level I trauma centers had better consent and conversion rates when compared to all other hospitals, 73 versus 55 per cent and 76 versus 61 per cent respectively, P < 0.0001 for both. The small, academic, trauma centers had the highest consent and conversion rates, 77 and 78 per cent, respectively, P < 0.0001 for both. Hospital characteristics such as academic involvement, Level I trauma designation, and size impact consent and conversion rates for potential organ donors. Small (<400 bed), academic, trauma centers have the highest consent rates and conversion rates. Factors for success in these institutions should be examined and applied to assist in improving donor rates across all types of hospitals.